2004
DOI: 10.1007/s10561-004-0503-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone defect repair in rat tibia by TGF-β1 and IGF-1 released from hydrogel scaffold

Abstract: Bone repair is one of the major challenges facing reconstructive surgery. Bone regeneration is needed for the repair of large defects and fractures. The ability of TGF-beta1 and IGF-1 incorporated into hydrogel scaffold to induce bone regeneration was evaluated in a rat tibia segmental defect model. External fixation was performed prior to the induction of the segmental bone defect in order to stabilize the defect site. Hydrogel scaffold containing either TGF-beta, IGF-1, TGF-beta + IGF-1, hydrogel containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Unfortunately, few studies compared the growth factor combination versus single IGF and TGF-b controls and their experimental setup varied greatly, in particular with respect to dose and delivery vehicle (Table 4). [85][86][87][88] Compared to TGF-b alone, nanogram dosages of the IGF/TGF-b combination in solution or released from gelatin hydrogels did not result in significantly enhanced mechanical properties or bone formation in rat marginal cortical defects, tibial defects, and mandibular defects, but the release of micrograms of the growth factor combination from a coated titanium implant enhanced the mechanical properties and callus formation in a rat tibial fracture model (Table 4).…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…Unfortunately, few studies compared the growth factor combination versus single IGF and TGF-b controls and their experimental setup varied greatly, in particular with respect to dose and delivery vehicle (Table 4). [85][86][87][88] Compared to TGF-b alone, nanogram dosages of the IGF/TGF-b combination in solution or released from gelatin hydrogels did not result in significantly enhanced mechanical properties or bone formation in rat marginal cortical defects, tibial defects, and mandibular defects, but the release of micrograms of the growth factor combination from a coated titanium implant enhanced the mechanical properties and callus formation in a rat tibial fracture model (Table 4).…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…The most notable ones are the bone morphogenic proteins (BMPs) that belong to the transforming growth factor beta superfamily, Hedgehog proteins, and Wnt proteins. Others include fibroblast growth factors (FGFs) and insulinlike growth factors (IGFs), which have positive effects on bone healing [44,55,83]. BMP-2 expression occurred in early periosteal callus just a few days after cortical bone fracture [11].…”
Section: Molecular Signals Control the Morphogenesis Of Periosteum Dumentioning
confidence: 99%
“…22,23 Studies on several in vivo bone repair models have also provided evidence for a proosteogenic role for TGFb. [24][25][26][27] Conversely, in immature cells, TGFb has an inhibitory effect. Alliston et al reported that TGFb inhibits osteoblast differentiation through Smad3-mediated suppression of Runx2 function and expression.…”
Section: Introductionmentioning
confidence: 99%